Baitul Jannah Islamic Boarding School Diplomacy in Increasing Economic Growth in Indonesia Through the Malaysia-to-Indonesia Crowdfunding Program - Siva Yunika; Diah Apriliani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Pesantren diplomacy is an increasingly important strategy in building international relations in the education and social sectors. This study aims to analyze the capabilities of Pondok Pesantren Baitul Jannah as a non-state actor in implementing partnership diplomacy and mobilizing sustainable support from donors in Malaysia, particularly through crowdfunding programs. This study uses a qualitative approach with a case study method to examine in depth the forms of diplomacy carried out. The main focus is to identify how Islamic boarding schools have succeeded in building relationships, obtaining financial and material support, as well as other resources. The results of the study show that the diplomacy of the Baitul Jannah Islamic boarding school is highly effective and adaptive. The success of this partnership is rooted in a strong social construction, based on the values of ukhuwah Islamiyah (Islamic brotherhood) and mutual trust generated through regular communication. This strengthened trust effectively creates strong institutional branding and enables the pesantren to act as a sub-national brand. Additionally, crowdfunding is identified as functioning strategically as an economic diplomacy tool, supported by digital transparency in financial reporting. This strategy demonstrates the ability of non-state actors to mitigate structural constraints, contribute significantly to the development of Islamic education, and fulfill the objectives of Public Diplomacy in shaping positive perceptions among foreign communities